VISUAL OUTCOME OF TRAUMATIC OPTIC NEUROPATHYAFTER STEROID TREATMENT IN KARIADI HOSPITAL - Roosdhantia, Isnia Rahmi; Riski Prihatningtias (Majalah Oftalmologi Indonesia, 2024)
Introduction: The occurrence of Traumatic Optic Neuropathy (TON) often occurs in the form of head injuries resulting from traffic accidents. TON is an important cause of impaired visual function which may be improved with steroid therapy. Objective: To determine the visual outcome in patients with TON treated with steroids in Kariadi Hospital, Semarang Methods: This research was a retrospective study. Thirty patients (20 males and 10 females) with TON in ophthalmology clinic, Kariadi Hospital Semarang between Januari 2019 and December 2020. Visual acuity, contrast sensitivity and color blindness test were included data from medical record. Steroid therapy were divided into 3 groups. Intraveous steroid injection alone, intravenous steroid followed with oral steroid, and oral steroid alone. The Wilcoxon and paired-t test as comparison test of pre-post therapy in one group and friedman test as comparison test in 3 groups. Results: There were 5 cases that received intravenous steroid, 18 cases received intravenous steroid with oral steroid, and 7 cases  received oral steroid. There were difference visual acuity in intravenous steroid with oral steroid (p = 0.001), visual acuity in oral steroid (p = 0.017), and color blindness test in intravenous steroid with oral steroid in pre-post therapy groups (p = 0.036). There were no difference in visual acuity, color blindness test, and contrast sensitivity between pre-post therapy groups when compared between 3 groups (p= 0.692, p =0.368, p=0.273). Conclusion: Patients with TON had better visual outcome after treated with intravenous steroid followed with oral steroid.